Assessing the optimality of euro adoption in Romania through shock correlations - Adrian Bodea (European Journal of Government and Economics (EJGE), 2021)
The present paper is concerned with the prospect of euro adoption in Romania. The study starts from the relevant literature of the Optimum Currency Areas and identifies the most widely acknowledged meta property and methodological model for this purpose: the SVAR Blanchard and Quah decomposition for identifying the supply and demand shocks. Employing the indicated model and the most recent data, we are able extract and analyse the underlying shocks that hit 34 European economic entities in the period 1995-2019, while also taking into account two crucial structural changes for the Romanian economy - central bank independence and EU accession. After performing the pairwise correlations between Romania and the rest of the economic entities for both the supply and demand disturbances, we map them on a bidimensional graph. We discover that while there is relevant integration and connectedness that ensures relatively high correlations between supply shocks, the politically-motivated monetary and fiscal policy disturbances that created ample and hectic demand side movements, are a factor of great concern for the prospect of single currency adoption in this Eastern European country. The findings support the view that there is room for the conduct of macro policies to become more supportive to the process of euro adoption and that the respect of convergence criteria would help in this respect. To our knowledge, this is the first study performing pairwise shock correlations between Romania and many other European economic entities, while also isolating the effect of post 2005 structural changes.
Keywords: E31; E32; E37; 330; optimum currency areas; SVAR; Blanchard and Quah decomposition; Romania; euro adoption; shock correlation